2023
DOI: 10.3390/healthcare11081187
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Health Care Delivery towards Value-Based Health Care in Germany: A Delphi Survey among Stakeholders

Abstract: Value-based healthcare (VBC) represents one strategy to meet growing challenges in healthcare systems. To date, VBC is not implemented broadly in the German healthcare system. A Delphi survey was conducted to explore stakeholders’ perspectives on the relevance and feasibility of actions and practices related to the implementation of VBC in the German healthcare system. Panellists were selected using purposive sampling. Two iterative online survey rounds were conducted which were preceded by a literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…More briefly, other studies conclude that the use of patient-reported outcome measures has itself been a stimulating factor for the implementation of VBHC [44]. Furthermore, the transparent display of health outcome information, so that it is available to both care providers and the general public, has also been shown to facilitate improvements in the health outcomes achieved [51]. In the same vein, other studies confirm that having a coding system to measure health outcomes in a subgroup of patients allows the team to critically examine processes and decisions in relation to different treatment regimens [42].…”
Section: Resulting Outcomes Of Implementing Value-based Carementioning
confidence: 99%
See 4 more Smart Citations
“…More briefly, other studies conclude that the use of patient-reported outcome measures has itself been a stimulating factor for the implementation of VBHC [44]. Furthermore, the transparent display of health outcome information, so that it is available to both care providers and the general public, has also been shown to facilitate improvements in the health outcomes achieved [51]. In the same vein, other studies confirm that having a coding system to measure health outcomes in a subgroup of patients allows the team to critically examine processes and decisions in relation to different treatment regimens [42].…”
Section: Resulting Outcomes Of Implementing Value-based Carementioning
confidence: 99%
“…---Krebs et al [51] Quantitative and qualitative -Involving patients or patient representatives; the accessibility of data; upto-date IT systems; multidisciplinary VBHC implementation teams.…”
Section: Steinman Et Al [50] Qualitativementioning
confidence: 99%
See 3 more Smart Citations